Revenue management for the hospitality industry - Hayes, David K.; Miller, Allisha A. (Hoboken, N.J. : Wiley, 2011)
"This is the first book that has been developed specifically to examine what revenue managers in the hospitality industry must know and do to be successful. Numerous cases and practical examples are used to illustrate revenue management concepts. Chapter ending questions and problems help them perform the calculations and practice the decision-making skills that are used in the field. RM in Action shows how the revenue management principles can be clearly illustrated using real-world examples reported in various news outlets. RM on the Web offers sites listed on the Internet to provide supplemental information about a topic or issue. Revenue managers will then gain hands-on skills to effectively manage their inventories and prices."--Provided by publisher.
"This is the first book that has been developed specifically to examine what revenue managers in the hospitality industry must know and do to be successful."--Provided by publisher.
Keywords: Hospitality industry -- Management; Hospitality industry